2007
DOI: 10.1007/s00244-006-0097-0
|View full text |Cite
|
Sign up to set email alerts
|

Liming Effects on Cadmium Stabilization in Upland Soil Affected by Gold Mining Activity

Abstract: To reduce cadmium (Cd) uptake of plants cultivated in heavy metal-contaminated soil, the best liming material was selected in the incubation test. The effect of the selected material was evaluated in the field. In the incubation experimentation, CaCO(3), Ca(OH)(2), CaSO(4).2H(2)O, and oyster shell meal were mixed with soil at rates corresponding to 0, 400, 800, 1600, 3200 mg Ca kg(-1). The limed soil was moistened to 70% of field moisture capacity, and incubated at 25 degrees C for 4 weeks. Ca(OH)(2) was found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(26 citation statements)
references
References 22 publications
0
21
0
5
Order By: Relevance
“…Many pot and field experiments have demonstrated that soil amendments such as lime, silicon fertilizer and phosphate could reduce rice uptake of heavy metals [16][17][18]. However, the inhibition effects varied according to the type and dose of soil amendments, experimental conditions and heavy metals.…”
Section: Introductionmentioning
confidence: 99%
“…Many pot and field experiments have demonstrated that soil amendments such as lime, silicon fertilizer and phosphate could reduce rice uptake of heavy metals [16][17][18]. However, the inhibition effects varied according to the type and dose of soil amendments, experimental conditions and heavy metals.…”
Section: Introductionmentioning
confidence: 99%
“…The nearby Amaranthus field (irrigated by well water as well as direct sewage water) and Marigold field (fertilized with treated sludge) were found with increasing level of cadmium Cadmium in soils can be immobilized by increasing the soil pH through addition of liming materials 20 . Decrease in cadium uptake arise from increased Cd 2+ adsorption caused by pH, increase in negative charge, thereby decreasing its bioavailability.…”
Section: Resultsmentioning
confidence: 99%
“…소석회의 시 용량을 최대 8 Mg/kg으로 시용하였을 때 무처리에 비해 각 부위별 카드뮴 흡수량은 알곡에서 64%, 볏짚에서 63.5%, 뿌 리에서 40%로 현저히 감소되어 졌다. 몇몇 연구자들이 밭토 양의 조건에서 소석회의 처리에 의해 식물체 내 카드뮴의 흡 수농도가 저감된다는 사실을 보고하였다 (Basta and Sloan, 1999;Gray et al, 1999;Hong et al, 2007). …”
Section: 토양 내 카드뮴 함량 및 화학적 특성unclassified
“…석회를 시용하여 토양 내 카드뮴의 용해도와 식물체 흡수를 저감시키기 위한 연구는 과거부터 오랜 기간 연구되어 왔으며 이미 국내외적으로 여 러 연구에서 석회의 효과를 입증해 왔다 (오왕근, 1981;이민효 등, 1984;정구복 등, 1999;김민경 등, 2004;Anderson and Siman, 1991;Kreutzer, 1995;Gray et al, 1999;Bolan et al, 2003;Hong et al, 2007). 그러나 토양 내 석 회처리에 의한 카드뮴의 부동화 기작에 대한 의견이 다양하 며 현장조건에서 석회처리에 의한 카드뮴의 식물이용성 저감 효과는 늘 의문시 되어왔다.…”
unclassified